TRACING THE EVOLUTION OF CASTE IN INDIA AND TAMIL NADU - K.Ebiraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Caste is a configuration of social stratification, through which communities are divided by numerous endogamous hereditary groups called ‘Jatis’. Caste principally operates on descent and hereditary. And its characteristics and features are determined by the individual’s birth. Caste stratifications in India are mainly administered in marriage, employment, housing, and general social interaction. These are reinforced through socioeconomic oppression, the threat of social exclusion, and physical violence. Many sociologists, orientalists, anthropologists, and historians have extensively studied the Indian caste system. This article tries to trace the evolution of caste in India and Tamil Nadu during different periods. It discusses how caste evolved from the ancient period and how it becomes rigid in the kings' period and how it functions along with politics in modern times.